Hidayah in the Process of Conversion to Islam in the Perspective of Muallaf - Achmad Maimun (IJIP : Indonesian Journal of Islamic Psychology, 2023)
In islamic teachings, Hidayah (Divine Guidance) becomes a fundamental aspect as it determines a person's salvation, especially for it in the hereafter. The ulemas, through a deductive approach, formulate hidayah comprehensively based on textual evidence. On the other hand, muallaf feels the presence of hidayah in their spiritual journey through the process of conversion. Based on this background, this study was aimed to formulate the concept of hidayah from the perspective of muallaf and to compare it with the perspective of the ulemas. To address these issues, a qualitative approach was used in this study. The primary method of data collection was in-depth interviews conducted with ten muallaf from diverse social, economic, and educational backgrounds. The findings of this research were as follows: hidayah comes illuminatively and requires sacrifice, Allah does not misguide humans but only provides guidance to them, and hidayah is a terra incognita. Furthermore, the results of comparing the perspectives of ulema and muallaf on hidayah were as follows: ulemas use a deductive-speculative approach, while muallaf use an inductive-empirical approach. The ulemas base their views on textual evidence, whereas muallaf rely on their psychological-spiritual experiences. Conceptually, the explanations provided by the ulemas regarding hidayah are more comprehensive and systematic, while the explanations by muallaf are simpler. In the aspect of Allah's will, muallaf believe that Allah does not misguide His believers, while ulemas hold a different view.